Management of tibia fracture by open reduction internal fixation and minimal invasive plate osteosynthesis in dogs - DIKSHA DHIMAN; AMIT KUMAR; S P TYAGI; ADARSH KUMAR; STANZIN; SIDHARTH SINGH; SANKALP MAHABALESH; ROHIT KUMAR; SUKHPREET SINGH (Indian Journal of Animal Sciences)
In the present study, tibia fracture in dogs were repaired by using two different fixation techniques, open reduction internal fixation (ORIF, Group 1, n=11) and minimal invasive plate osteosynthesis (MIPO, Group 2, n=8). Various factors such as age, bodyweight, fracture type, soft tissue trauma, severity, post-operative care and fixation technique governs fracture healing. Majority of the factors were kept similar other than fixation technique, for an unbiased comparison between the two treatment groups, i.e. ORIF and MIPO. The mean duration of surgery was significantly more in group 1 (ORIF, 107.7±6.61) whereas it was nearly half of the time in group 2 (MIPO, 31.8±4.12). No significant difference between the fracture gap, plate length, plate bridging ratio and plate span ratio was noticed in the two groups. The working length of plates applied in the MIPO group (45.7±2.4) was longer than in the ORIF group (23.2±4.96) and there was statistically significant difference in the screw density between both the groups. Fractured tibia was 4.8% shorter than contralateral limb in MIPO group whereas in ORIF group fractured limb was 3.2% shorter than the contralateral limb. The MIPO group showed an early ambulation, i.e. 5.24±0.63 days in comparison to ORIF group (11.60±2.8 days). The radiographic time to union (days) was shorter in group 2 (MIPO, 38.1±12.5) as compare to group 1 (ORIF, 76.2±10.34).